А. Chekhov in the works of Zhang Jie - Vladimir A. Meskin; Huizhen Zhang (RUDN Journal of Studies in Literature and Journalism)
The purpose of this paper is to examine the genesis of the work of Zhang Jie, a major Chinese prose writer of the second half of the 20th and early 21st century. The authors of the article quote the writer’s repeated acknowledgements of the enormous influence that Anton Pavlovich Chekhov had on her work, but most importantly, they try to determine in what exactly, at what levels of form and content this influence manifested itself. Correlations in sphere of genre and thematic formations, poetic techniques and essential dominants of Russian writer’s style, which later appeared quite clearly in Zhang Jie’s works, are revealed: restraint, brevity, lyricism, and ‘objectivity’ as it was understood by the Russian classicist. The article speaks of the presence in Zhang Jie’s works of Chekhov’s characteristic motifs, Chekhov’s ambivalent attitude to ‘the little man’, Chekhov’s exposure of vulgarity, and condemnation of slave psychology. At the same time, the flexibility of perception of artistic thought of the predecessor, elements of dialogue in the circumstances of modern times, and national specifics are noted. Significant assistance in writing the article was provided by reference to Chekhov’s collection of works on literary labor, a translation of which was published in China in the mid-20th century and which was undoubtedly carefully read by Zhang Jie. The present study based on the works of A. Veselovsky on genetic and typological aspects of interaction between literatures of different peoples allowed us to conclude about the determining role of A. Chekhov in the formation of Zhang Jie’s writing. The article is intended to contribute to the study of the dialogue of cultures.